Las colaboraciones de Rubén Darío en la revista salvadoreña "La Quincena" - Letona, René (Anales de Literatura Hispanoamericana, 2003)
The article deals with the relations between Rubén Darío and El Salvador. As example, it describes the Salvadoran magazine La Quincena, whose description is based on the existent copies in the Municipal Newspaper Library of Madrid; they belong to years 1904- 1905. It tells about Darío contributions, and besides tells about an unknown Francisco Gavidia article, which is very important and related to Darío and the modernism, for that reason is reproduced as annex. It also other mentions modernist authors and texts, which were published in the magazine.